Computed Tomography Imaging Characteristics of Neck Paragangliomas: A Retrospective Analysis: Retrospective study on CT parameters of neck paragangliomas. - Ravishankar, Dev; Sunil, Devika (Scripta Medica, 2024)
Background/Aim: Paragangliomas are rare neuroendocrine tumours arising from paraganglia of the autonomic nervous system. Computed tomography (CT) imaging plays a crucial role in the evaluation and characterisation of neck paragangliomas. This retrospective study aimed to analyse the CT imaging features of neck paragangliomas to enhance diagnostic accuracy and delineate the radiological characteristics associated with these tumours.Methods: A retrospective review of CT imaging studies of patients diagnosed with neck paragangliomas from March 2021 to October 2023 was conducted. Imaging characteristics including tumour location, size, enhancement pattern, vascularity, calcifications, adjacent tissue involvement and relationship with surrounding structures were analysed.Results: A total of 87 patients with histologically confirmed neck paragangliomas were included in the study. CT imaging revealed typical findings of neck paragangliomas ie well-defined hyper-vascular masses with avid contrast enhancement, commonly located at the carotid bifurcation or along the carotid sheath. In addition, characteristic flow voids and the presence of feeding vessels were observed on CT angiography in a significant number of cases. The imaging analysis also identified calcifications and encasement of adjacent structures as frequent features of advanced-stage paragangliomas.Conclusions: CT imaging of neck paragangliomas demonstrated consistent radiological features, including hypervascularity, contrast enhancement and distinct anatomic locations. Knowledge of these imaging characteristics is essential for accurate diagnosis and preoperative planning. Recognition of these features on CT imaging can aid in differentiating paragangliomas from other neck masses and facilitate appropriate management strategies.